2021
DOI: 10.1097/gme.0000000000001789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative serum vitamin D levels on early clinical function outcomes and the moderate-to-severe pain prevalence in postmenopausal women after primary total knee arthroplasty

Abstract: Objective:To investigate the impact of vitamin D levels on early clinical function outcomes and the potential risk factors of moderate-to-severe pain prevalence in postmenopausal women after primary total knee arthroplasty (TKA).Methods:From April 2017 to December 2019, 226 women were retrospectively recruited. The women were divided into two groups based on their preoperative serum 25-hydroxyvitamin D levels: (1) vitamin D-sufficient group (≥30 ng/mL); (2) vitamin D-deficient group (<30 ng/mL). The visual ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…It has been proven that implant survival was significantly better in people taking a combination of calcium and vitamin D (at a dose of 800 IU or more) for more than 1 year compared to those who had never used it ( p < 0.001) [ 20 ]. Song et al (2021) [ 21 ] undertook to investigate the effect of vitamin D levels on early clinical function outcomes and potential risk factors for moderate to severe pain in postmenopausal women after TKA. The study included 226 women who were included in the group: the group with normal serum vitamin D concentration (level ≥ 30 ng/mL) and the group with vitamin D deficiency (level < 30 ng/mL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that implant survival was significantly better in people taking a combination of calcium and vitamin D (at a dose of 800 IU or more) for more than 1 year compared to those who had never used it ( p < 0.001) [ 20 ]. Song et al (2021) [ 21 ] undertook to investigate the effect of vitamin D levels on early clinical function outcomes and potential risk factors for moderate to severe pain in postmenopausal women after TKA. The study included 226 women who were included in the group: the group with normal serum vitamin D concentration (level ≥ 30 ng/mL) and the group with vitamin D deficiency (level < 30 ng/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The study included 226 women who were included in the group: the group with normal serum vitamin D concentration (level ≥ 30 ng/mL) and the group with vitamin D deficiency (level < 30 ng/mL). Although there was no significant difference in preoperative assessment of clinical function between the two groups, the authors concluded that vitamin D deficiency may adversely affect early functional outcomes in postmenopausal women after TKA and may be considered as a risk factor for moderate to severe postoperative knee pain (in correlation with smoking and high mass index) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reported that vitamin D deficiency was a risk factor for postoperative pain at 3 months after surgery. 8 However, in an observational study, Bose et al did not observe a link between vitamin D levels and postoperative pain after laparoscopic bariatric surgery. 20 This discrepancy may be attributed to differences in patient populations, particularly in terms of vitamin D levels and the types of surgery performed.…”
Section: Discussionmentioning
confidence: 96%
“…3,6,7 Several studies have reported that vitamin D deficiency is associated with musculoskeletal pain, cancer pain, postoperative pain, and post-traumatic pain. [8][9][10][11][12][13][14][15] Low vitamin D levels have been linked with higher opioid use and an increased risk of opioid use disorders in patients undergoing common surgical procedures. 10,16 Two meta-analyses of randomized controlled trials (RCTs) highlighted a correlation between vitamin D supplementation and pain reduction.…”
Section: Introductionmentioning
confidence: 99%
“…It could also inhibit diabetes-induced retinal leukostasis and leakage. Taking all of this together, one action of PPAR-γ is considered capable of reducing the progression of DR [51,52]. Finding that one of the missense mutations (rs1801282 C/G, known as Pro12Ala, and quite common in some populations) could influence the risk of insulin resistance and influences lipid metabolism [53] focused the attention of researchers working with DR risk factors.…”
Section: Chromosomementioning
confidence: 99%